(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2019)
Today the gap between students and teachers is growing. On the one side, students want to be engaged with methodologies that they recognize as their own, that is multimedia. On the other side, teachers very often have no deep understanding of new technologies. Some teachers can build creative presentations, but they very rarely can build engaging multimedia educational tools to teach and test their students’ knowledge. To overcome the difficulties of the teachers in creating their own multimedia interactive educational tools, a simple programming environment, BloP, has been built. BloP has been tested in several educational tasks, such as teaching foreign languages or telling stories. New multimedia tools, that have been designed by using BloP, have been built in just a few weeks by students of a non-scientific degree. The tools have been very well accepted by users and have shown effective in improving their performances in the intended tasks. This experiment shows that even non-technical teachers could quickly and easily build their own multimedia educational tools by using specifically tailored environments and that those tools can be effective in improving the student’s engagement and their performances.